SHARIAH ANALYSIS OF E-COMMERCE TRANSACTIONS FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS - Suci Hayati; Husnul Fatarib (International Journal Labs, 2022)
Background: Technological developments have had an impact on changes in daily living habits, people who used to shop at traditional markets are now switching to e-commerce because they are considered more effective, efficient and also cheaper. The impact of technological developments extends to Indonesia. This is marked by the proliferation of e-commerce businesses. Objective: The aim is to find out the security and shariah of e-commerce transactions in the perspective of Islamic economics. Therefore, researchers are interested in conducting research with the title